Aortic Wall Thickness and Amniotic Fluid Albuminuria in Growth-Restricted Twin Fetuses. (25th March 2013) - Zanardo, Vincenzo; Visentin, Silvia; Bertin, Martina; Zaninotto, Martina; Trevisanuto, Daniele; Cavallin, Francesco; Cosmi, Erich
Abstract : Background and objective: Intrauterine growth restriction (IUGR) may be associated with significantly higher aortic intima–media thickening (aIMT) values. It is unknown if fetal aIMT is associated with glomerulosclerosis and amniotic albuminuria in utero. Design, setting, participants, and measurements : Fetal abdominal aIMT and amniotic albumin/creatinine ratio (ACR) were measured in 126 individual twin fetuses, recruited by the Obstetrics and Gynaecology Clinics of the University of Padua (Italy) Medical Center. The IUGR twin fetuses were classified into two groups: Group A were those fetuses whose estimated fetal weight (EFW) was <10th percentile with pulsatility index >2 SD and Group B were those fetuses whose EFW was <10th percentile and had no velocimetry abnormalities. Results : The median fetal aIMT was significantly different in the three groups (Group A = 0.9 mm; Group B = 0.7 mm; and appropriate for gestational age (AGA) = 0.5 mm; p < .0001). It was significantly higher in Group A than in the AGA group ( p < .0001) and than in the Group B fetuses ( p = .003), respectively. In addition, ACR was different in the three groups (Group A = 183, 500 mg/g; Group B = 6, 4720 mg/g; and AGA = 8, 2750 mg/g; p = .0002). It was significantly higher in Group A than in the AGA group ( p = .03) and than in Group B ( p = .02), respectively. Conclusions: Growth-restricted twin fetuses with velocimetry abnormalities present are associated with aIMT and higher ACR levels in amniotic fluid, which could be possible markers in utero of preclinical atherosclerosis, and early glomerulosclerosis.